Table of Content - - (Journal of Curriculum and Teaching Methodology, 2024)
Table of Content:1. The degree to which social studies teachers in the South Al Sharqiyah Governorate in the Sultanate of Oman possess the skills of employing artificial intelligence in educationFahad Salem Saif Almasrouri2. The level of teaching practices among Arabic language teachers for the intermediate stage in light of the sustainable development goals in Makkah Al-MukarramahDr. Mashael Saleh Al-Dosari, Noura Abdullah Al-Zahrani3. A Proposal for Developing the Textbook of Hadith and Islamic Education for First Grade  in Secondary Schools in Saudi ArabiaFahad Odeh Awad Alatwi, Dr. Iman Mohamed Mabrouk Qutb4. The reality of including the dimensions of digital citizenship in the courses of my eternal language in the intermediate stage in the Kingdom of Saudi ArabiaDr. Mashael Saleh Al-Dosari, Ms. Azza Hashem Al-Zahrani5. The effect of a proposed unit in science based on PISA standards in developing life problem-solving skills among Prep school studentsDr. Naglaa Fauzy Esmaeil Alkest, Prof. Mahmoud Ebrahim Taha, Dr. Mohamed Mostafa Ghalwash
Keywords: Journal of Curriculum and Teaching Methodology